The effect of strain rate of steel material - Ahmad Firdaus Mohd Sabri
This final year project presents the effect of strain rate of steel material. Two different experiments are required in order to investigate the effect of strain rate of steel material.The first experiment is using Universal Testing Machine to investigate the effect of strain rate at static condition while the second experiment is using Split Hopkinson bar technique to investigate the effect of strain rate at dynamic condition.